STUDY OF WAVE DOMINANT DIRECTIONS ON SEDIMENT TRANSPORT IN THE ESTUARY OF KAPUAS RIVER, PONTIANAK, WEST KALIMANTAN - Budiman, Farid; Danial, Mochammad Meddy; Meirany, Jasisca; Lestari, Arfena Deah; Bachtiar, Vivi (Fakultas Teknik Universitas Tanjungpura, 2023)
The Kapuas River is a very important water transportation route in West Kalimantan, crossing 5 districts and 1 city. The problem that occurs in the shipping lane on the Kapuas River is the accumulation of severe sediment at the mouth of the estuary. This becomes an obstacle for ships with large loads to sail, for this reason, this research was carried out. The purpose of this study was to determine the dominant direction of waves and sediment transport. This study was calculated using the CERC (Coastal Engineering Research Centre) method and using secondary data. It was found that the dominant wave direction came from the North (N) direction with an incidence percentage of 22.496%. Percentage of occurrence from the Northwest (NW) direction is 12.145%, from the West (W) direction is 6.253%, and from the Southwest direction (SW) is 11.724%. While the amount of sediment transport from the Northwest is -393062.1306 m3/year with the characteristics of the sediment being clay, from the West it is -250.1672 m3/year with the sediment characteristics being silty clay and from the Southwest, it is 579090.2782 m3/year with sediment characteristics of silty clay. The results of the sediment calculation have negative results which indicate that there is no sediment transport from the Northwest and West, but the sediment is deposited. For this reason, it is necessary to carry out appropriate handling of these problems to reduce sediment build-up in the study area.